Asymptotic analysis of Sturm-Liouville problem with Robin and two-point boundary conditions - Štikonas, Artūras (Lietuvos matematikos rinkinys, 2022)
We analyze the initial value problem and get asymptotic expansions for solution. We investigate the characteristic equation for Sturm-Liouville problem with one classical Robin type boundary condition and another two-point nonlocal boundary condition. Finally, we obtain asymptotic expansions for eigenvalues and eigenfunctions.